DAMPAK PENERAPAN SISTEM E-PAJAK DAN KEKUATAN ISOMORFIK TERHADAP KEPATUHAN PAJAK - Nugraheni, Agustina Prativi; Sitoresmi, Mumpuni Wahyudiarti; Khabibah, Nibras Anny (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Tax revenue can be optimized when taxpayers comply with tax regulations. The government is taking various initiatives to make it easier for taxpayers to fulfill their tax obligations, including the use of electronic tax payment systems. The purpose of this study is to analyze the effects of attitude toward electronic taxation, adoption of electronic taxation, and isomorphism intensity on tax compliance. The research sample consists of SME taxpayers in Magelang. Data were collected by questionnaire and analyzed using SEM-PLS. The results indicate that attitude toward electronic taxation has a positive but not significant impact on tax compliance. On the other hand, the introduction of electronic tax payment system and isomorphic intensity affect tax compliance. This study contributes to the literature on electronic tax systems and tax compliance.